Distinctive Sedimentary Evolution at the East Edge of the Central Yellow Sea Mud Over the Past 45 kyr: Evidence From Detrital Mineralogy - Zhang, Yao; Meng, Xianwei; Han, Zongzhu; Jin, Bingfu; Lai, Zhiqing; Liu, Jinqing (Frontiers in Earth Science, 2022)
Central Yellow Sea mud (CYSM) is a vital part of the coastal sand and distal mud depositional system in the South Yellow Sea (SYS). Previous studies concerning the sedimentary evolution of this area have almost exclusively concentrated on its interior during the Holocene instead of its periphery. In this paper, we used a sediment core (H10), with a significantly slow sedimentary rate, to reconstruct the sedimentary evolution at the east edge of the CYSM since MIS3a ( 45 kyr). This mainly involved using detrital minerals, the chemical compositions of garnet, and grain size. The provenance of coarser sediments has remarkable Yellow River-derived characteristics, especially during MIS2 and MIS1. The sedimentary evolution was primarily controlled by hydrodynamic regimes accompanied by changes in relative sea levels (RSLs) and climate. During MIS3a, frequent RSL fluctuations and powerful tidal current erosion were responsible for two facie shifts from the neritic sea to the shore and the lower sedimentary rate in the study area. A paleo-cold water mass and muddy deposition occurred during the high RSL stages with authigenic pyrite enrichment. During MIS2, the paleo-Yellow River was distributed on the SYS and flowed through the study area. Fluvial deposition on the shelf may be eroded by the strong winter monsoon with an extremely dry and cold climate. Since 9.6 kyr, intense hydrodynamic regimes, which were induced by tidal current and upwelling, were responsible for the very much thin deposition, and coarser sediments remained in the study area. Notably, combined with previous-studied cores, a much more detailed and intuitional cognition for CYSM formation can be obtained via our special perspective: mud periphery. This study elucidates the sedimentary systems evolution and mud area formation of continental shelf seas.